An Analysis of Politeness Strategies Used by The Main Characters (Western And Chinese) in The Karate Kid Movie by Harald Zwart - Nur Wahyuni; Dwijani Ratnadewi; Armeria Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
This research observedÂ the dialogue between the characters in The Karate Kid Movie which consists of characters from America (West) and China (East). It has purpose to find out the kinds of politeness strategies which are used by the main characters, and describe how and why they are used by the main characters. This research is qualitative research. The data are in the form of utterances. There are many politeness strategies which are usedÂ by the main characters. In the bald on record strategy, there are three utterances found. Then, there are twelve utterances that include positive politeness strategy, while there is one utterance that includes negative politeness strategy, and there is one utterance contains off record strategy. It can be concluded that the main characters often use positive politeness strategies in their conversation. The result of this study can be concluded that the politeness strategies are important to be used in life. It means that it can be used to avoid and minimize the Face Threatening Acts which a speaker makes. Besides, it can be used to avoid misunderstanding in the conversation of daily life.